Molecular landscape and targeted therapy of acute myeloid leukemia - Runxia Gu; Xue Yang; Hui Wei (BMC, 2018)
Abstract For decades, genetic aberrations including chromosome and molecular abnormalities are important diagnostic and prognostic factors in acute myeloid leukemia (AML). ATRA and imatinib have been successfully used in AML and chronic myelogenous leukemia, which proved that targeted therapy by identifying molecular lesions could improve leukemia outcomes. Recent advances in next generation sequencing have revealed molecular landscape of AML, presenting us with many molecular abnormalities. The individual prognostic information derived from a specific mutation could be modified by other molecular lesions. Therefore, the genomic complexity in AML poses a huge challenge to successful translation into more accurate risk stratification and targeted therapy. Herein, a summary of these mutations and targeted therapies are described. We focus on the prognostic information of recent identified molecular lesions and emerging targeted therapy.